Characterization of short- and medium-chain chlorinated paraffins in outdoor/indoor PM10/PM2.5/PM1.0 in Beijing, China. (June 2017) - Huang, Huiting; Gao, Lirong; Xia, Dan; Qiao, Lin; Wang, Runhua; Su, Guijin; Liu, Wenbin; Liu, Guorui; Zheng, Minghui
Abstract: Persistent organic pollutants (POPs) were listed in the Stockholm Convention, because of their adverse health effects, persistence, bioaccumulation and ubiquitous presence in the environment. Short chain chlorinated paraffins (SCCPs), chlorinated derivatives of n-alkanes, have been listed as candidate POPs under Stockholm Convention. Inhalation uptake was an important exposure pathway for non-occupational adult human and the pollution of particle matter has caused great concern. There are some studies focused on POPs such as polychlorinated biphenyls, polychlorinated dibenzo-p-dioxins and dibenzofurans and polybrominated diphenyl ethers in different size particles. However, there were no studies that discussed CP concentrations in particulate matter (PM) with different sizes. In this study, a total of 30 PM samples were collected both outdoors and indoors at a sampling site in Beijing. These samples were used to investigate the concentrations and distributions of SCCPs and medium chain chlorinated paraffins (MCCPs) in PM fractions of different sizes, and to evaluate inhalation exposure risks. The results showed that the average SCCPs and MCCPs in the outdoor PM10 were 23.9 and 3.6 ng m −3, while the mean values in indoor were 61.1 and 6.9 ng m −3, respectively. The levels of SCCPs and MCCPs in indoor and outdoor were relatively high. SCCP and MCCP concentrations in the indoor PM10 /PM2.5 /PM1.0 samples were higher than the corresponding values in the outdoor, because of the using of some products containing CPs in the indoors, like paints and coatings, leather and rubber products. In both outdoor and indoor air, CPs are mainly associated with particles ≤2.5 μm in diameter. The main homolog groups for both SCCPs and MCCPs were C10–11 Cl7–8 . It is assumed that SCCPs in the outdoor and indoor PM samples may mainly derive from the production and use of CP-42 and CP-52. Graphical abstract: Highlights: The average SCCP concentrations were higher than the appropriate MCCPs in the indoor and outdoor PM samples. SCCP and MCCP concentrations in the indoor PM10 /PM2.5 /PM1 samples were higher than the corresponding values in the outdoor. In both outdoor and indoor air, CPs are mainly associated with particles ≤2.5 μm in diameter.